2012
DOI: 10.1083/jcb.201112132
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 promotes nucleotide excision repair through DDB2 stabilization and recruitment of ALC1

Abstract: PARP1-mediated poly(ADP-ribosyl)ation of DDB2 prolongs its occupation on UV-damaged chromatin and promotes the recruitment of the chromatin remodeler ALC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
227
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(239 citation statements)
references
References 58 publications
9
227
1
2
Order By: Relevance
“…The N-terminal DNA binding domain of PARP-1 that is known to be recruited to DNA strand breaks 20 was also recruited to UV-lesions without strand breaks, indicating more general property of this domain of PARP-1 to bind to different types of DNA damages. Our model is also consistent with previously reported interactions of DDB2 and PARP-1 at the UV-lesion site 5,7 . We have earlier shown that PARP-1 and DDB2 co-immunoprecipitate at the UV-damaged chromatin in the presence of ethidium bromide, indicating their direct interaction on the same DNA strand 7 .…”
Section: No Effect Of Parp-1 and Ddb2 Binding On Cpd-photolyase Mediasupporting
confidence: 93%
See 2 more Smart Citations
“…The N-terminal DNA binding domain of PARP-1 that is known to be recruited to DNA strand breaks 20 was also recruited to UV-lesions without strand breaks, indicating more general property of this domain of PARP-1 to bind to different types of DNA damages. Our model is also consistent with previously reported interactions of DDB2 and PARP-1 at the UV-lesion site 5,7 . We have earlier shown that PARP-1 and DDB2 co-immunoprecipitate at the UV-damaged chromatin in the presence of ethidium bromide, indicating their direct interaction on the same DNA strand 7 .…”
Section: No Effect Of Parp-1 and Ddb2 Binding On Cpd-photolyase Mediasupporting
confidence: 93%
“…The key reason is that the existing methodologies that readily identify interactions of PARP-1 with DNA strand breaks are not sufficiently sensitive to study the relatively weaker responses of PARP-1 to DNA damage without strand breaks. The response of PARP-1 to UVC-induced direct photolesions, such as cyclobutane pyrimidine dimers (CPD) that are formed without any DNA strand breaks exemplifies this problem.Recent studies from others and our team have shown the involvement of PARP-1 in the host cell reactivation 4 and specifically in the nucleotide excision repair (NER) of UV-damaged DNA through its interaction with early NER protein DDB2 [5][6][7] . Additional studies have shown that downstream NER proteins XPA 8,9 and XPC 10 are PARylated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus we compared early recruitment dynamics of PARP1 and ALC1, both of which are known as fast recruiters with maximum recruitment reached within < 1 min [1517,29,48,49] (Figure 7). …”
Section: Resultsmentioning
confidence: 99%
“…Previous reports showed that CEES induced DNA mono adducts are predominantly repaired by BER and NER pathways (Jowsey et al, 2009;Matijasevic et al, 2001). PARylation plays an active role in both repair pathway, potentially by being activated through DNA strand breaks introduced by endonucleases as intermediates during the repair processes (Fischer et al, 2014;Pines et al, 2013Pines et al, , 2012Robert et al, 2013). Thus, even though mustards do not induce DNA strand breaks directly, strand breaks can occur in response to mustard treatment by enzymatic processes that actively introduce them in the course of repair processes, thereby triggering PARP activation.…”
Section: Application Of the Optimized Cees Treatment Prototocol For Tmentioning
confidence: 99%